2021
DOI: 10.1007/jhep11(2021)177
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Extremal Surfaces and the Holographic Entropy Cone

Abstract: Quantum states with geometric duals are known to satisfy a stricter set of entropy inequalities than those obeyed by general quantum systems. The set of allowed entropies derived using the Ryu-Takayanagi (RT) formula defines the Holographic Entropy Cone (HEC). These inequalities are no longer satisfied once general quantum corrections are included by employing the Quantum Extremal Surface (QES) prescription. Nevertheless, the structure of the QES formula allows for a controlled study of how quantum contributio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…Our preliminary results suggest that the monogamy of mutual information can be derived using our quantum generalization of the max multiflow theorem, as was done in the classical case [64], although requiring a 'geometrization condition' for the bulk entropies. This is a sufficient condition in our proof, however, it certainly seems stronger than bulk JHEP02(2022)180 MMI (see, however [110]). There are reasons to further investigate this question, however, in order to clarify the consistency conditions of double holographic scenarios.…”
Section: Jhep02(2022)180mentioning
confidence: 77%
See 1 more Smart Citation
“…Our preliminary results suggest that the monogamy of mutual information can be derived using our quantum generalization of the max multiflow theorem, as was done in the classical case [64], although requiring a 'geometrization condition' for the bulk entropies. This is a sufficient condition in our proof, however, it certainly seems stronger than bulk JHEP02(2022)180 MMI (see, however [110]). There are reasons to further investigate this question, however, in order to clarify the consistency conditions of double holographic scenarios.…”
Section: Jhep02(2022)180mentioning
confidence: 77%
“…Very recently we became aware of[110] which claims that bulk monogamy is indeed enough to ensure boundary monogamy.…”
mentioning
confidence: 99%
“…Other interesting classes of quantum states and constructs have been studied in the past, which suffer from the same rapidly increasing complexity as n increases. It would be interesting to explore if, upon symmetrizations, one can gain some further knowledge about the general-n structure of the cone of stabilizer states [28], the cone of linear rank inequalities [29], the cone of hypergraph entropies [30][31][32], the cone of topological links [33], or even the HEC under quantum corrections from bulk matter fields [34].…”
Section: Discussionmentioning
confidence: 99%
“…The RT/HRT and maximin prescription has led to stronger inequalities on the von Neumann entropy that do not hold for non holographic systems [64][65][66][67]. These inequalities haven't been shown to hold when we include quantum corrections via the QES prescription, however exploration in this direction was initiated in [87] where it was shown that if the bulk entropies obey the monogamy of mutual information [64] then the dual boundary entropies also obey the same.…”
Section: Maximin Vs Extremal: Strong Sub-additivity and Entanglement ...mentioning
confidence: 99%